Assessment of physical literacy in 8- to 12-year-old Pakistani school children: reliability and cross-validation of the Canadian assessment of physical literacy-2 (CAPL-2) in South Punjab, Pakistan - Syed Ghufran Hadier; Yinghai Liu; Liu Long; Syed Muhammad Zeeshan Haider Hamdani; Haris Khurram; Syed Danish Hamdani; Shaista Shireen Danish; Syeda Urooj Fatima (BMC, 2024)
Abstract Background The increasing prevalence of physical inactivity, declining fitness, and rising childhood obesity highlight the importance of physical literacy (PL), as a foundational component for fostering lifelong health and active lifestyle. This recognition necessitates the development of effective tools for PL assessment that are applicable across diverse cultural landscapes. Aim This study aimed to translate the Canadian Assessment of Physical Literacy-2 (CAPL-2) into Urdu and adapt it for the Pakistani cultural context, to assess PL among children aged 8-12 years in Pakistan. Method The Urdu version of CAPL-2 was administered among 1,360 children aged 8-12 from 87 higher secondary schools across three divisions in South Punjab province, Pakistan. Statistical analysis includes test-retest reliability and construct validity, employing confirmatory factor analysis to evaluate the tool's performance both overall and within specific subdomains. Results The Urdu version of CAPL-2 demonstrated strong content validity, with a Content Validity Ratio of 0.89. Confirmatory factor analysis supported the four-factor structure proposed by the original developers, evidenced by excellent model fit indices (GFI = 0.984, CFI = 0.979, TLI = 0.969, RMSEA = 0.041). High internal consistency was observed across all domains (α = 0.988 to 0.995), with significant correlations among most, excluding the Knowledge and Understanding domains. Notably, gender and age significantly influenced performance, with boys generally scoring higher than girls, with few exceptions. Conclusion This study marks a significant step in the cross-cultural adaptation of PL assessment tools, successfully validating the CAPL-2 Urdu version for the Pakistani context for the first time. The findings affirm the tool's suitability for assessing PL among Pakistani children, evidencing its validity and reliability across the Pakistani population.